THE FUNCTIONS OF FLOATING MAXIM THAT UTTERED BY CHARACTERS OF THE HUNGER GAMES MOVIE - Adiari, Ni Putu Yuana Jelita; Maharani, Putu Devi; Utami, Ni Made Verayanti (LPPM Universitas Dhyana Pura, 2021)
ABSTRACTBased on Grice's theory (1989), cooperative principle makes communication becomeunderstandable so that the meaning of the utterances can be well received by the interlocutor.However, in daily lives, this principle is often floated by the speaker and interlocutor becausesometimes the speakers want the interlocutor to get the meaning of the utterances that cannotbe expressed explicitly. This violation is known as floating maxim. This study aims to explorethe functions of floating maxims that occurs in conversations between characters in the movieentitled The Hunger Games. The function refers to the speech act theory, in which Searle(1979) states that there are five points of speech acts, namely functioning as representative,directive, commissive, expressive and declarative. The methods used in this research areobservational and qualitative methods, by watching movies and reading the script of themovie’s conversation while taking notes the conversations that contain floating maxim,classifying the functions of floating maxim occurred by Searle's (1979) theory and supportedby theory of context situation by Halliday (1985). The results of this study indicate that thereare 30 floating maxim obtained, 19 data (63%) have function as representatives, five data(17%) have function as directive statements, one data (3%) has function as commissivestatements and 5 data (17%) have functions as expressive utterance.Keywords: Floating maxim, function, movieABSTRAKDalam teori Grice (1989), prinsip kerjasama dalam sebuah komunikasi akan membantukomunikasi menjadi lancar dan dimengerti oleh penutur dan mitra tutur sehingga maksud dariujaran dapat diterima baik. Namun dalam kesehariannya, prinsip ini sering dilanggar olehmitra tutur karena penutur ingin mitra tutur menangkap maksud ujarannya yang tidak bisadiutarakan secara eksplisit. Pelanggaran ini dikenal dengan pelanggaran maksim. Penelitianini bertujuan untuk mencari fungsi pelanggaran maksim yang terjadi dalam percakapan antartokoh pada film berjudul The Hunger Games. Fungsi yang dimaksud mengacu pada teoritindak tutur, yang mana Searle (1979) menyebutkan ada lima poin tindak tutur yakni berfungsisebagai representatif, direktif, komisif, ekspresif dan deklaratif. Metode yang digunakan dalampenelitian ini adalah metode observasi dan kualitatif, dengan cara menonton film danmencatat percakapan yang mengandung pelanggaran maksim, mengklasifikasikan fungsipelanggaran maksim dengan teori Searle (1979) yang didukung dengan teori konteks olehHalliday (1985). Hasil penelitian ini menunjukkan dari 30 pelanggaran maksim yangdiperoleh, terdapat 19 data (63%) berfungsi sebagai representatif, lima data (17%) berfungsisebagai pernyataan direktif, satu data (3%) berfungsi sebagai pernyataan komisif dan 5 data(17%) berfungsi sebaai pernyataan ekspresif.Kata kunci: Pelanggaran maksim, fungsi, film